2015
DOI: 10.1016/j.anorl.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-associated lymphoepithelial carcinoma of the larynx

Abstract: Lymphoepithelial carcinoma of the larynx is rare. Immunohistochemical examination is essential for the positive diagnosis. Epstein-Barr virus-associated lymphoepithelial carcinoma has been exceptionally reported. The radiosensitivity of this tumour allows conservative first-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…A variety of other names have also been attributed to this tumor category, such as undifferentiated carcinoma of nasopharyngeal type, undifferentiated carcinoma with lymphoid stroma, lymphoepithelioma and lymphoepithelial like carcinoma, as well as recent names like lymphoepithelial carcinoma (LEC). Recently, Acuna, Hammas and Kermani have highlighted the etiopathogenesis of the disease in the background of viral etiology [ 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of other names have also been attributed to this tumor category, such as undifferentiated carcinoma of nasopharyngeal type, undifferentiated carcinoma with lymphoid stroma, lymphoepithelioma and lymphoepithelial like carcinoma, as well as recent names like lymphoepithelial carcinoma (LEC). Recently, Acuna, Hammas and Kermani have highlighted the etiopathogenesis of the disease in the background of viral etiology [ 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Keeping in view the poor outcome owing to distant metastasis, the role of induction chemotherapy has still remained controversial. Kermani used neoadjuvant chemotherapy with a response rate of 30% at the primary site and 50% at regional nodes [ 13 ]. Neo-adjuvant chemotherapy has been recommended in a few studies to reduce the disease volume in a clinically positive lymph node and to decrease the risk of distant failures [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunostaining with melanocyte differentiation markers (HMB45 or Melan-A) and lymphoid markers is useful to eliminate melanoma and lymphoma respectively. Nasopharyngeal carcinoma with laryngeal metastasis must also be eliminated [ 5 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…lacrimal and salivary glands, esophagus, pancreas and middle ear. [70][71][72][73][74][75] Notably, our recent review on LEC of uterine cervix revealed no EBV infection in cancer cells in this rare primary cervical malignancy 76 .…”
Section: Status Of Ebv In Colorectal Cancermentioning
confidence: 99%